2019
DOI: 10.2147/cmar.s223201
|View full text |Cite
|
Sign up to set email alerts
|

<p>Integrin α5/ITGA5 Promotes The Proliferation, Migration, Invasion And Progression Of Oral Squamous Carcinoma By Epithelial–Mesenchymal Transition</p>

Abstract: Background: Integrin signalling is involved in cell migration, invasion, proliferation and motility. Integrin α5/ITGA5 is a subunit of Integrin and contributes to the activation of Integrin signalling. The potential role of Integrin α5/ITGA5 in oral squamous cancer remains unknown. The aim of this study was to uncover the effect and mechanism of Integrin α5/ ITGA5 in the progression of oral squamous carcinoma. Method: TCGA database scanning, qRT-PCR, immunohistochemistry and Western blotting assays were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 25 publications
1
35
0
Order By: Relevance
“…11 Altered expression of ITGA5 has been demonstrated in certain cancers, including colorectal, breast, and oral cancers. [12][13][14] In this study, we confirmed that miR-27b was significantly downregulated while ITGA5 was significantly upregulated in TSCC. Then, we showed that miR-27b inhibited the proliferation, migration, and invasion of TSCC cells in vitro and suppressed tumor growth in vivo.…”
Section: Introductionsupporting
confidence: 74%
“…11 Altered expression of ITGA5 has been demonstrated in certain cancers, including colorectal, breast, and oral cancers. [12][13][14] In this study, we confirmed that miR-27b was significantly downregulated while ITGA5 was significantly upregulated in TSCC. Then, we showed that miR-27b inhibited the proliferation, migration, and invasion of TSCC cells in vitro and suppressed tumor growth in vivo.…”
Section: Introductionsupporting
confidence: 74%
“…These genes have also been relevant in other tumor types. For example, ITGA5, an integrin that promotes tumor invasion 70 , has been correlated with lower survival of lung cancer patients 71 , and it also functions as a receptor for FN1 72 , 73 , which was also upregulated in our coculture. IL4R induces a prometastatic phenotype in epithelial tumors.…”
Section: Discussionmentioning
confidence: 79%
“…University and was conducted following the Declaration of Helsinki (certi cation no. Quick-PJ 2020- [11][12][13][14]. All patients provided written informed consent.…”
Section: Discussionmentioning
confidence: 99%
“…This work was approved by the Academic Committee of The First A liated Hospital of Anhui Medical University (certi cation no. Quick-PJ 2020- [11][12][13][14] and was conducted following the Declaration of Helsinki.…”
Section: Clinical Tissue Specimensmentioning
confidence: 99%